Grammarly: An Online EFL Writing Companion - N. M. F. Amin Mubarok; Ahmad Syafii (STKIP Al Hikmah Surabaya, 2021)
Writing becomes one of fundamental skills in learning language. In tis digital era, when everything is possible to be done in online, the students prefer to easily find some references in the websites or other online sources. The students hesitate to produce their own ideas in that they can get anything they want on the internet. This cases take a big part of the quality of the students in mastering writing skill. Thus, the teachers should have many alternative to help the students, more to EFL stuents to improve their writing performance through such an online based-learning. Grammarly is one of possible solution can be taken as the students writing assistant while the teachers giving some exercises. The students will be helpful working on Grammarly in that they will be able to produce any languages they know, then Grammarly will take a place to help them correct their work.